Myeloid- and hepatocyte-specific deletion of group VIA calcium-independent phospholipase A2 leads to dichotomous opposing phenotypes during MCD diet-induced NASH - Jansakun, Chutima; Chunglok, Warangkana; Altamura, Sandro; Muckenthaler, Martina; Staffer, Simone; Tuma-Kellner, Sabine; Merle, Uta; Chamulitrat, Walee (Biochimica et biophysica acta. Molecular basis of disease, 2023)
Polymorphisms of phospholipase A2VIA (iPLA2β or PLA2G6) are associated with body weights and blood C-reactive protein. The role of iPLA2β/PLA2G6 in non-alcoholic steatohepatitis (NASH) is still elusive because female iPla2β-null mice showed attenuated hepatic steatosis but exacerbated hepatic fibrosis after feeding with methionine- and choline-deficient diet (MCDD). Herein, female mice with myeloid- (MPla2g6−/−) and hepatocyte- (LPla2g6−/−) specific PLA2G6 deletion were generated and phenotyped after MCDD feeding. Without any effects on hepatic steatosis, MCDD-fed MPla2g6−/− mice showed further exaggeration of liver inflammation and fibrosis as well as elevation of plasma TNFα, CCL2, and circulating monocytes. Bone-marrow-derived macrophages (BMDMs) from MPla2g6−/− mice displayed upregulation of PPARγ and CEBPα proteins, and elevated release of IL6 and CXCL1 under LPS stimulation. LPS-stimulated BMDMs from MCDD-fed MPla2g6−/− mice showed suppressed expression of M1 Tnfa and Il6, but marked upregulation of M2 Arg1, Chil3, IL10, and IL13 as well as chemokine receptors Ccr2 and Ccr5. This in vitro shift was associated with exaggeration of hepatic M1/M2 cytokines, chemokines/chemokine receptors, and fibrosis genes. Contrarily, MCDD-fed LPla2g6−/− mice showed a complete protection which was associated with upregulation of Ppara/PPARα and attenuated expression of Pparg/PPARγ, fatty-acid uptake, triglyceride synthesis, and de novo lipogenesis genes. Interestingly, LPla2g6−/− mice fed with chow or MCDD displayed an attenuation of blood monocytes and elevation of anti-inflammatory lipoxin A4 in plasma and liver. Thus, PLA2G6 inactivation specifically in myeloid cells and hepatocytes led to opposing phenotypes in female mice undergoing NASH. Hepatocyte-specific PLA2G6 inhibitors may be further developed for treatment of this disease.
Available online 2 November 2022
Gesehen am 26.01.2023